Factors That Influence the Time of Labor in The 2nd Class of Mothers - Tutik Iswanti; Nintinjri Husnida; Hani Sutianingsih (Jurnal teknologi Kesehatan Borneo, 2022)
Stage II is the period of the expulsion of the baby, starting from the complete opening until the baby is born. If the second stage lasts long, there will be symptoms such as dehydration, infection, maternal fatigue, and intrauterine fetal death. This study's objective is to determine the factors that affect the duration of second-stage labor for mothers giving birth. This study is a secondary study with a total sample of 87 respondents. The sampling method in this study used a systematic sampling technique, namely systematic sampling. After calculating with the formula, the interval value is 11, so the sample taken from some of the population is a multiple of 11 numbers, and then the data were analyzed. Results of the study are Maternal labor who experienced a long period II was 8.0%, age at risk was 24.1%, primigravida was 32.2%, uterine inertia was 13.8%, PROM was 12.6%, fetal weight was not normal by 2,3%, and the length of the first period is 32,2%. The factors that affect the second period are contraction (P-value ≤ 0,001) and the first period (P-value = 0.033). The factors that did not affect were age (P-value = 1,000), parity (P-value = 0.421), PROM (P-value = 0.214) and fetal weight (P-value = 1,000). The factor of the duration of the first stage had the strongest effect on the second delivery stage in mothers with an OR of 0.074. Factors that influence the second stage are contraction and the duration of the I stage.